Second Ave. Dawson. - Howard, Mart Albert, 1855-1926 (Manuscripts, Archives, and Special Collections, Washington State University Libraries: https://libraries.wsu.edu/masc, 1898)
1 Lantern Slide: b&w; 10 x 8 cm. Second avenue of Dawson, Yukon Territory. Photo by Howard. 341.